The moderating role of perceived injustice in the relationship between being envied and social undermining in public sector organizations - Yarivand, Mohammad; Al-shahrani, Hend Faye; Hammad, Mohammad Ahmed; Malakouti, Meraj (Frontiers in Psychology, 2025)
PurposeSocial undermining in the workplace—subtle behaviors that hinder success and damage professional relationships—has been widely studied. However, the role of envy in driving social undermining, particularly from the perspective of the person being envied, remains underexplored. This study examines how being envied influences social undermining behaviors and tests whether perceived injustice moderates this relationship within Tehran’s public sector.MethodsA cross-sectional design with purposive sampling was employed. A web-based questionnaire was completed by 342 full-time Iranian civil servants. Data were analyzed using path analysis and bootstrapping procedures to test direct and moderated relationships.ResultsBeing the target of envy was positively associated with social undermining, and this relationship was significantly strengthened under conditions of high perceived injustice. Furthermore, higher levels of social undermining correlated with increased psychological distress and lower life satisfaction.ConclusionThe findings demonstrate the destructive impact of envy and perceived injustice on employees in Iranian governmental organizations. Organizations should implement fairness-enhancing policies and interventions to mitigate envy-driven undermining and safeguard employee well-being.